Development and Validation of Healthy School Indicators Based on Al-Islam Kemuhammadiyahan in Sidenreng Rappang Regency - Said, Sunandar; Kamal, Kamal; Mardhatillah, Mardhatillah; Ramlan, Pratiwi; Sulaiman, Zulkarnain; Febrianti, Devy; Adri, Khaeriyah; Kusumawati, Dwi Erma (Poltekita: Jurnal Ilmu Kesehatan, 2025)
This study aims to develop and validate healthy school indicators based on Al-Islam Kemuhammadiyahan (AIK) in Sidenreng Rappang Regency. The research employs a mixed-method approach with Sequential Explanatory Research design. The qualitative phase involves in-depth interviews with Muhammadiyah scholars to explore AIK's perspective on health and identify initial healthy school indicators. The quantitative phase validates these indicators through a cross-sectional study using a questionnaire distributed to Muhammadiyah schools in Sidenreng Rappang. Confirmatory Factor Analysis (CFA) was used to assess the validity and reliability of the indicators. The findings reveal four main pillars of health from the AIK perspective: physical, mental, spiritual, and environmental health. The developed indicators include balanced nutrition programs, regular physical activity, counseling, religious education, and environmental management. CFA results indicate that the indicators are valid and reliable, with Composite Reliability (CR) and Average Variance Extracted (AVE) meeting the required standards. The implementation of these indicators is expected to create a holistic health-supportive school environment, reinforcing students' physical, mental, spiritual, and environmental well-being. This study significantly contributes to the development of healthy school concepts in Indonesia, aligned with Islamic values, and provides a foundation for health policy and programs in Islamic-based schools to enhance overall student health and well-being.